2003
DOI: 10.1002/humu.10297
|View full text |Cite
|
Sign up to set email alerts
|

A genetic polymorphism in the coding region of the gastric intrinsic factor gene (GIF) is associated with congenital intrinsic factor deficiency

Abstract: Congenital intrinsic factor (IF) deficiency is a disorder characterized by megaloblastic anemia due to the absence of gastric IF (GIF, GenBank NM_005142) and GIF antibodies, with probable autosomal recessive inheritance. Most of the reported patients are isolated cases without genetic studies of the parents or siblings. Complete exonic sequences were determined from the PCR products generated from genomic DNA of five affected individuals. All probands had the identical variant (g.68A>G) in the second position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…This analysis resulted in an observed allele frequency of 11.9% for the c.68G allele compared with 6.7% among 30 German newborns and 3.8% among 131 Spanish newborns as reported in ref. 24. Although the observed differences in frequency are likely just variations between populations, our results suggest that homozygosity for the c.68G polymorphism has no clinical significance in IFD.…”
Section: Discussionmentioning
confidence: 50%
“…This analysis resulted in an observed allele frequency of 11.9% for the c.68G allele compared with 6.7% among 30 German newborns and 3.8% among 131 Spanish newborns as reported in ref. 24. Although the observed differences in frequency are likely just variations between populations, our results suggest that homozygosity for the c.68G polymorphism has no clinical significance in IFD.…”
Section: Discussionmentioning
confidence: 50%
“…A number of other single mutations leading to loss of function and polymorphisms have been identified (Tanner et al , 2005). Polymorphism in exon 1 (Q5R) was reported in four patients with low IF (Gordon et al , 2004). However, a larger study has identified this polymorphism at a frequency of 3–11% and may not be associated with decreased IF production (Ament et al , 2009) or low Cbl (Remacha et al , 2008).…”
Section: Absorption Of Cobalaminmentioning
confidence: 99%
“…Th e congenital form is a rare disorder characterized by mutations in the IF gene localized on chromosome 11q13 and lack of IF production. In congenital IF defi ciency, gastric acid secretion and mucosal cytology are normal [74][75][76] . Th e acquired pernicious anemia, in most cases, is an autoimmune disorder characterized by chronic atrophic gastritis and reduced IF production due to the presence of autoantibodies against gastric parietal cells [73,77] .…”
Section: Vitamin B 12 Defi Ciencymentioning
confidence: 99%